2023
DOI: 10.3233/jnd-230012
|View full text |Cite
|
Sign up to set email alerts
|

Full-Length SMN Transcript in Extracellular Vesicles as Biomarker in Individuals with Spinal Muscular Atrophy Type 2 Treated with Nusinersen

Abstract: Background: Three therapeutic strategies have radically changed the therapeutic scenario for spinal muscular atrophy (SMA). However, therapeutic response differs between individuals. There is a need to identify biomarkers to further assess therapeutic response and to better understand which variables determine the extent of response. Methods: We conducted a study using an optimized digital droplet PCR-based method for the ultra-sensitive detection of SMN transcript in serum EVs from SMA 2 individuals treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…Idem, in a study involving patients treated with nusinersen, an increase in SMN-FL levels in extracellular vesicles blood was observed after 14 months of treatment (60). In the first-in-human study with risdiplam, it was shown that FL SMN2 mRNA levels and SMN protein levels increase in whole blood after treatment (56,57).…”
Section: Response Biomarkermentioning
confidence: 98%
See 1 more Smart Citation
“…Idem, in a study involving patients treated with nusinersen, an increase in SMN-FL levels in extracellular vesicles blood was observed after 14 months of treatment (60). In the first-in-human study with risdiplam, it was shown that FL SMN2 mRNA levels and SMN protein levels increase in whole blood after treatment (56,57).…”
Section: Response Biomarkermentioning
confidence: 98%
“…The Biomarkers for SMA (BforSMA) study is an example of this effort. It was a cross-sectional omics study that evaluated blood and urine protein analytes in children (age 2-12 years) with genetically confirmed SMA and age-matched healthy controls (60). A resulting 200 candidate biomarkers were found to correlate with motor scores, and the most significant markers across all outcome measures were plasma protein analytes.…”
Section: Omics and Other Circulating Proteinsmentioning
confidence: 99%
“…Table 2 demonstrates that NfL and pNfH were used as potential pharmacodynamic (response) biomarkers in the majority of studies that examined the utility of molecular biomarkers for monitoring therapeutic response in SMA. In the majority of studies, a decrease in NfL and pNfH levels was observed following treatment with nusinersen [39,[61][62][63][76][77][78][79][80][81], whereas others observed no change in the levels of these biomarkers [45,56,60,[82][83][84] (Table 2).…”
Section: Monitoring Of Therapeutic Response In Sma Using Molecular Bi...mentioning
confidence: 99%